Like night and day: channelling desires through landscapes and nightscapes - Savela Timo (United Kingdom, 2025)
This article examines differences between landscapes and nightscapes, i.e. how what we encounter in daylight conditions differs considerably from what we encounter in the dark. I explore what landscape is and how it works, followed by examining how it and how it works is negated by darkness, only to be re-established through illumination. The purpose of this article is to illustrate how nightscapes are, in fact, superior to landscapes in terms of channelling people’s desires. While darkness prevents the abstract machine of landscape from functioning, illumination returns it to action, providing those with the necessary capital the opportunity to influence people and shape their identities. Nightscapes do, however, provide opportunities to anyone who wishes to express oneself by utilising the illumination provided by others for their own purposes and, at times, against the others.